Effect of Seed Soaking Time In KNO3 on Germination, Vegetative Morphology, and Results of Bambara Chicken (Vigna Subterranea (L.) Verdcourt) - Sari, Aulia Ika; Zakiya, Aulia; Zainudin, Agus (Journal of Tropical Crop Science and Technology, 2023)
The The bambara groundnut has the potential to continue to be developed, but the obstacle faced is the very limited availability of bambara groundnut seeds. This is because there are no varieties from the results of breeding that are released and the low quality of the seeds. Low seed quality is caused by slow germination and results in the seed growth process being non-unison, this is influenced by seed dormancy. The purpose of this study was to determine the effect of soaking time in KNO3 on germination, vegetative morphology, and crop yield in the field by measuring seed viability and vigor, vegetative morphology and yield. The research was carried out for 4 months, from June-October 2022 which took place at the Agrotechnology Laboratory of the Muhammadiyah University of Malang and Dadaprejo Land, Batu City. The study was conducted using a simple Completely Randomized Block Design (RKLT) consisting of 10 treatments, and was repeated 3 times. The observed variables included moisture content, DB, PTM, IV, KCT, T50, plant height, number of leaves, leaf shape, leaf color, stem color, pod color, pod shape, number of pods, pod dry weight, number of seeds, dry weight seeds, yield potential, and weight of 1000 seeds. The results showed that the long soaking of seeds in KNO3 did not affect their vegetative morphology. Soaking time of seeds in KNO3 had no significant effect on DB and PTM values, but had a very significant effect on IV values, the number of leaves in the vegetative and generative phases. And it has a significant effect on the height of the KCT, T50, and plant height in the vegetative phase. As for the yield variable, the results showed no significant effect. Soaking time in KNO3 only affected germination, plant height, and number of bambara groundnut leaves.